Modeling professional and pedagogical training of teachers of natural sciences to the profession in specialized schools (Pedagogy of Higher and Secondary Education, 2012)
Onipko V. Modeling professional and pedagogical training of teachers of natural sciences to the profession in specialized schools.The article discusses the scientific basis of modeling the process of preparing future teachers, it is theoretically justified by the use of modern multi-layer model of teacher education in the highest, specificity is determined by the construction of the sandwich model of vocational and educational training of future teachers of natural sciences to the professional profile in high school.
Keywords: higher education teacher education; the future teacher of natural sciences; simulation training; the sandwich model; profile high school